Scientific Approach in Cognitive Conflict Strategy: Effects on Cognitive Learning Outcomes Based on the Assertive Attitude of High School Students - Salbiatun Khoeriah; Widha Sunarno; Pujayanto Pujayanto (Universitas Sebelas Maret, 2024)
Distance learning requires teachers to determine and use appropriate learning methods, models, and strategies. However, the lack of variety in these three things makes students less active. The research objectives include finding out whether or not there are: 1) difference the influence of the application of cognitive conflict learning strategies and mind mapping with a scientific approach on students' cognitive learning outcomes, 2) the difference in the influence of high and low category students' assertive attitudes on students' cognitive learning outcomes, and 3) the interaction of the influence between the use of learning strategies and assertive attitudes on the results Cognitive learning for class The research method applies experiments through a 2x2 factorial design. The population includes all class XI MIPA students, comprising five classes and totals 166 students. Samples were taken from 2 classes from 5 classes. The sampling technique refers to Cluster Random Sampling. Data collection techniques are done through documentation, tests, and questionnaires. The data analysis technique uses prerequisite tests, namely the normality and homogeneity tests. Next, a hypothesis test was carried out using a two-way ANOVA with unequal cell contents. The results of the research are that there are differences in the influence of the use of cognitive conflict learning strategies and mind mapping using a scientific approach on students' cognitive learning outcomes (F observation = 4.227 > F table = F 0.05; 1; 53 = 4.02); t there is a difference in the influence of assertive attitudes of students in the high and low categories on students' cognitive learning outcomes (F observation = 7.265 > F table = F 0.05;1;53 = 4.02); and there is no interaction effect of the use of learning strategies with an assertive attitude on students' cognitive learning outcomes (F observation = 0.809 < F table = F 0.05; 1; 53 = 4.02). This study’s contribution the effectiveness of applying cognitive conflict learning strategies and mind mapping through a scientific approach to Cognitive learning outcomes on Elasticity and Hooke's Law material.